The tenant of Wildfell Hall - Brontë, Anne, 1820-1849. (Wingfield, S. Aust. : Cameron House, 2008)
"First published in 1848, a novel in which a woman flees from a disastrous marriage with her child to a desolate moorland mansion. It portrays one woman's struggle for independence at a time when law and society defined a married woman as her husband's property."--Provided by publisher.
Keywords: Landlord and tenant -- Fiction; Married women -- Fiction; Alcoholism -- Fiction; England -- Fiction